Diskursus Fiqh 4 Mazhab Tentang Keraguan Niat Dalam Shalat: Studi Pemahaman Mahasiswa UIN Sumatera Utara - Zali, Muhammad (STAI Darul Qalam Tangerang, 2025)
This study aims to examine the issue of students’ doubts regarding the intention (niyyah) in prayer. The main problem identified is the gap between theoretical knowledge of fiqh of worship and the students’ everyday spiritual practice. This research employs a qualitative method with a descriptive-analytical approach. Data were collected through observation, interviews, and documentation, and analyzed using the stages of data reduction, data display, and conclusion drawing. The findings indicate that the doubts experienced by students of FKM UIN Sumatera Utara are influenced by the lack of continuous spiritual guidance within the campus environment, the low level of fiqh literacy, and the tendency to perceive worship merely as a formal obligation. The study underscores the need for strengthening applied fiqh literacy and integrating spiritual development into the campus curriculum, so that students may not only understand intention in its normative dimension but also internalize it consciously in their worship practices.